A escolha dos modelos de sistemas produto-serviço: um estudo de caso na geração de energia fotovoltaica - Langoski, Leandro Marcio (Universidade do Vale do Rio dos Sinos, 2017)
This thesis approaches the Product-Service Systems (PSS), an innovation strategy with the purpose of integrating product and service in order to meet customer needs and reducing environmental impacts. The empirical object is the generation of photovoltaic energy, and, by using the case study, works with two types of PSS: the product-oriented and the use-oriented. With REN 482/2012, ANEEL allowed the distributed generation, that is, a residence, industry or enterprise can generate their own energy. The thesis analyzes how to choose a PSS in the generation of photovoltaic energy. For this, three parties are investigated: electric power distributors, companies that sell PV power generation equipment and consumers (legal entity). Some items are discussed in the analysis, such as the tactics of implementing a PSS (contracts, marketing, product and service design, and network of the actors), sustainability and the electric energy chain in Brazil. The results indicate that technological innovations, long-term equipment and the traditional market model can influence the choice of a PSS and, thus, determine the business model.
Keywords: Sistemas Produto-Serviço (PSS); Energia fotovoltaica; Geração distribuída; Sustentabilidade; Produc-Service Systems (PSS); Photovoltaic energy; Distributed generation; Sustainability; ACCNPQ::Ciências Sociais Aplicadas::Administração